Heavy metals Cu, Zn, Cd and Pb in tissue, liver of Esox lucius and sediment from the Anzali international lagoon- Iran - Imanpour Namin, J. (Caspian Journal of Environmental Sciences, 2011)
Levels of contaminants in fish are of particular interest because of the potential risk to humans consuming them. This paper examines the levels of cadmium, lead, zinc and copper in liver and muscle tissue of Esox lucius and in sediments from the Anzali international wetland in Iran. The wetland is a nursery and feeding habitat for fish species both from the lagoon and the Caspian Sea, which are consumed by the local inhabitants and others. Eleven main rivers discharge agricultural, industrial, urban and municipal wastes into this wetland. Twenty five Esox lucius specimens, with a mean weight of 804.6±121g and mean length of 430.7± 2mm were collected from the wetland by multimesh gill nets in September and December 2007.. The age was determined from scale samples according to the annual ring structure. Average concentrations of Cd, Cu, Pb and Zn accumulated in the mid-dorsal muscle tissue (filleted and skinned) of fish were 0.001, 0.21±0.02, 0.13±0.01 and 2.55±0.18 µg.g-1, respectively. The concentrations of these metals in liver samples were Cd: 0.0014± Cu: 0.96± 0.61, Pb: 0.11 ± 0.04 and Zn: 2.46±1.5 µg.g-1. Significant positive correlations were detected between Zn and Cu with body weight, while negative correlations were found between Pb and body weight. The concentrations of Zn, Cu and Cd were below the maximum allowable concentrations for fish proposed by WHO and MAFF (safe for human consumption) but concentration of Pb exceeded the standard levels.